Perception of intensive care unit stressors by patients in Malaysian federal territory hospitals. - Soh, Kim Lam; Soh, Kim Geok; Ahmad, Zaiton; Abdul Raman, Rosna; Japar, Salimah (e-Content Management, 2008)
The Intensive Care Unit (ICU) is a therapeutic place for monitoring critically ill patients. However, it is a stressful area for the patients and it is causing them great anxiety. Previous studies have identified three groups of stressors in ICU namely; physical, psychological and environmental.The aims of this study were to determine the ICU stressors as experienced by patients and to determine the level of stressors felt by patients in ICU. A cross sectional study was done on 70 patients from two tertiary hospitals in Malaysia. A face-to-face interview with structured questionnaire was used for patients. Data collection occurred from 15 December 2006 to 31 January 2007.The five major ICU stressors perceived by patients were pain, being stuck with needles, boredom, missing their spouses and being too hot/cold.The ICU physical stressors were the major items ranked by post ICU patients.The findings from this study provided a set of baseline information to the health care providers, particularly ICU nurses in Malaysia, with which to provide better care for the patients in ICU.